The Influence of Application of Video Based Learning Media on Student Learning Outcomes - Adita Kusumawati, Erna (Mudir : Jurnal Manajemen Pendidikan, 2023)
The aim of this research is to use video-based educational media during classroom instruction to enhance student academic achievements. The researchers employed a quasi-experimental design with a classical experimental approach. According to the statistical data analysis, students in the experimental group (class C) demonstrated a significant improvement in pretest-posttest scores compared to the control group (class B). The experimental group's average pretest score was 51, while their posttest score was 83. Additionally, the n-gain test indicated an average increase of 0.7, with over 10 students meeting the high n-gain criteria, resulting in 89.5% of students achieving KKM in the posttest. On the other hand, only one student met the high n-gain criteria in the control group, and more than 70% of students achieved KKM in the posttest. The results of the t-test conducted using SPSS showed that t-count > t-table, which implies that Ha was accepted and Ho was rejected.